Enamel surface roughness in young permanent tooth after bleaching - Ardini, Yunita Dewi; Wati, Hera; Budi W, Teguh (Sekretariat Pengurus Besar, Persatuan Doktor Gigi Indonesia, 2007)
Bleaching for children is rarely performed in dental clinic, but the literature indicates that bleaching is used for children. Bleaching causes demineralization that can increase enamel surface roughness. However, the addition of fluoride and potassium nitarte can inhibit mineral loss and activate remineralization. The aim of this in vitro study is to evaluate the surface roughness of young permanent tooth enamel submitted to bleaching with 10% carbamide peroxide and 10% carbamide peroxide containing potassium nitrate and fluoride. Materials and Methods: fourteen dental blocks (5x5mm2) from young permanent teeth (premolar) with polished enamel surface were randomly assigned to 2 treatment group (n=7), as follows: 10% CP (Group 1) and 10% CP+PF (Group II). During fourteen days, each enamel surface was daily exposed to 1 hour bleaching regimen followed by storage in artificial saliva. Surface roughness (Ra) was measured before (baseline) and immediately after bleaching (fourteen days) with surface roughness tester (SRT) and by electron microscope (SRME). Data analyzed by paired t-test (statistically significant differences (p<0.05)were observed among the groups after bleaching compared to baseline. By independent t-test, statistically significant differences were reported between 10%CP and 10%CP+PF (p<0.05). Though of bleaching agents are able to alter the enamel surface roughness but the increase of enamel surface roughness of all groups presented is still considered normal. Ra value 10%CP>10%CP+PF. In conclusion, bleaching with 10% CP increases surface roughness. However, the increase of Ra values was low and may not be clinically significant.